Plasma levels of natriuretic peptides and development of chronic kidney disease. Issue 1 (December 2015) - Ogawa, Noriyuki; Komura, Hiroshi; Kuwasako, Kenji; Kitamura, Kazuo; Kato, Johji
Abstract Background Plasma levels of atrial and brain natriuretic peptides (ANP and BNP) are increased in patients with chronic kidney disease (CKD) complicated with deteriorated kidney function, but the relationship between the plasma level of ANP or BNP and the future development of CKD is unclear. Methods We measured the plasma ANP and BNP levels of 294 local residents without CKD in a Japanese community (56.5 ± 10.4 years, mean ± S.D.), who were followed up for the development of CKD over the next 7 years. Results Sixty-three residents developed CKD during the follow-up period, and the baseline level of plasma ANP of these residents was significantly higher than in those without CKD development. Kaplan-Meier analysis showed that the residents with higher ANP than the median value developed CKD more frequently than those with lower ANP. The association between plasma ANP level and CKD development was found to be independent of baseline estimated glomerular filtration rate by a Cox proportional hazards model, while this association became insignificant when adjusted by age; plasma ANP was significantly correlated with age. Compared with ANP, the relationship between plasma BNP and CKD development was unclear in these analyses. Conclusions Age-related elevation of plasma ANP levels preceded the development of CKD in the general population of Japan, raising a possibility for ANP being involved in the development of CKD.